1841 A Four-Year Retrospective Study of the Safety and Efficacy of Palivizumab in High Risk Infants. (October 2012) - Abusamra, R; Schofield, M; Minasian, C
Abstract : Aim: A four year retrospective review of safety and efficacy of Palivizumab in the prophylaxis of respiratory syncytial virus (RSV) in high risk infants. Background: RSV is the leading viral pathogen responsible for hospitalization with lower respiratory tract infection in high risk infants A previous study reported a 55% reduction in RSV related hospitalizations with passive immunoprophylaxis with Paluvizimab 1 . Methods: A retrospective study of all high risk infants requiring Palivizumab between 2006 and 2010. Inclusion criteria included children under 2 years with chronic lung disease on home oxygen, those with congenital immunodeficiency and infants under 6 months with confirmed congenital heart disease. Children received intramuscular injections of Palivizimab every 28days during the RSV season (October-March). Data was collected on demographics, underlying diagnosis, side-effects and confirmed RSV infection. A cost analysis was also performed. Results: Records on 61 patients were examined. 15 children did not meet the study criteria. Data on RSV infection was available for 52/61 patients. Of these children, none of those who received a complete course of prophylaxis developed RSV infection. Reported side-effects were mild with the exception of one child with a seizure disorder who had an increase in fit frequency. Having dedicated clinics for administering Palivizimab, allowed sharing of opened vials between patients and more effective utilization of clinic staff and resources. Conclusions: RSV prophylaxis is safe and effective in preventing RSV infection in high risk infants. Further strategies have been used to reduce drug costs and improve cost-effectiveness.